2013
DOI: 10.1016/j.bbamem.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative stress on plasma membrane fluidity of THP-1 induced macrophages

Abstract: Plasma membrane is one of the preferential targets of reactive oxygen species which cause lipid peroxidation. This process modifies membrane properties such as membrane fluidity, a very important physical feature known to modulate membrane protein localization and function. The aim of this study is to evaluate the effect of oxidative stress on plasma membrane fluidity regionalization of single living THP-1 macrophages. These cells were oxidized with H(2)O(2) at different concentrations, and plasma membrane flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 54 publications
3
84
1
Order By: Relevance
“…1b, c. Fluorescent probes, including C11--BODIPY 581/591 , normally change their excitation and emission spectra when in aggregate forms or upon strong cell--cell interactions, changes in membrane fluidity, loss of lipid raft integrity, and/or mechanical stress (de la Haba et al 2012;Verstraeten et al 2010). Nevertheless, by limiting cell--cell interactions in 5 × 10 5 cell/well cultures, C11--BODIPY 581/591 (at a final concentration of 3.2 μM) was properly challenged by ROS/RNS generated by activated neutrophils, and the dose--dependent effect of AST (a powerful antioxidant) was adequately evidenced (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1b, c. Fluorescent probes, including C11--BODIPY 581/591 , normally change their excitation and emission spectra when in aggregate forms or upon strong cell--cell interactions, changes in membrane fluidity, loss of lipid raft integrity, and/or mechanical stress (de la Haba et al 2012;Verstraeten et al 2010). Nevertheless, by limiting cell--cell interactions in 5 × 10 5 cell/well cultures, C11--BODIPY 581/591 (at a final concentration of 3.2 μM) was properly challenged by ROS/RNS generated by activated neutrophils, and the dose--dependent effect of AST (a powerful antioxidant) was adequately evidenced (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymatic activity of desaturases and elongases can directly affect membrane fluidity by increasing the abundance of MUFA and PUFA in membrane phospholipids [45]. Moreover, non-enzymatic peroxidation transforms unsaturated fatty acids, mainly PUFA, into oxidized metabolites, altering membrane composition and properties [17,19,49,50]. Concomitantly, PUFA metabolites activate several signaling pathways, either in protective or detrimental manners [6,8,19,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, membrane fluidity and phase separation have a pivotal role in the potency of ligand binding to membrane receptors, on direct cell-cell interaction and on the modulation of the activity of membrane enzymes, receptors, channels, and transporters [16]. Membrane fluidity alterations have been indeed described in various pathologies, such as thrombocythemia, hyperlipidemia, hypercholesterolemia, hypertension, diabetes mellitus, obesity, sepsis, allergies, and burn injuries, in cases of alcohol abuse, in Alzheimer's disease and in schizophrenia [17][18][19]. In addition to the effects of lipids as signaling molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that membrane oxidation changes the general properties of the plasma membrane and that peptide translocation does not directly involve oxidized species. For instance, membrane oxidation can alter membrane fluidity, and this alone could change the permeability of the cell (57,58). In addition, Melikov et al (59) have suggested that surface-exposed phosphatidylserine (PS) mediates the translocation of polyarginine peptides into cells.…”
Section: Discussionmentioning
confidence: 99%